2020
DOI: 10.1149/1945-7111/ab856b
|View full text |Cite
|
Sign up to set email alerts
|

Review—Conducting Polymer-Based Binders for Lithium-Ion Batteries and Beyond

Abstract: In the search for active Lithium-ion battery materials with ever-increasing energy density, the limits of conventional auxiliary materials, such as binders and conducting additives are being tested. Binders adhere to active substances and current collectors, yielding an interconnected electrode structure that ensures mechanical integrity during the (de-)lithiation process. Even though the battery binder only accounts for a fraction of battery weight and cost, it is a bottleneck technology in the deployment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
132
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(134 citation statements)
references
References 187 publications
0
132
0
2
Order By: Relevance
“…Using conductive polymer binders as both binder and conductive agent are expected to maintain the overall electrode conductivity, and meanwhile boost the energy density of cell by increasing the proportion of active material in the electrode. Many reports have demonstrated that the conductive polymer binders with high electrical conductivity and strong binding ability can promote improved cycling performances of Si‐based anodes at high areal capacities 178‐180 …”
Section: Designing Of Polymer Binders For Si‐based Anodesmentioning
confidence: 99%
“…Using conductive polymer binders as both binder and conductive agent are expected to maintain the overall electrode conductivity, and meanwhile boost the energy density of cell by increasing the proportion of active material in the electrode. Many reports have demonstrated that the conductive polymer binders with high electrical conductivity and strong binding ability can promote improved cycling performances of Si‐based anodes at high areal capacities 178‐180 …”
Section: Designing Of Polymer Binders For Si‐based Anodesmentioning
confidence: 99%
“…From this contrast three regions can be differentiated: the crystalline LATP grains, thin and darker semi-amorphous regions to both sides at the crystalline grain interface, and a brighter amorphous region in the grain boundary center. Both grains are oriented in [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] hex zone axis. The highly symmetric bright reflexes in Figure 1c correspond to a [100] pc pseudocubic sublattice commonly assigned to partially occupied Li positions in the LATP crystal structure.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…This is mainly due to mechanochemical, chemical, and electrochemical stability issues and interfacial processes that have severely compromised any proposed cell's lifetime. [7][8][9][10][11] While many SSE material inherent (mechano-)chemical processing issues seem amenable to modern engineering approaches, [12][13][14][15][16][17][18][19] the situation is less bright regarding the control of interfacial chemical and electrochemical stability (especially when featuring a LMA), as well as ionic and electronic transport quantities across these interfaces. A hitherto missing deep understanding of the structural, chemical, and physical properties of the buried solid-solid interfaces inside ASSBs at the atomic level is required to overcome these performance limiting interfacial issues.The most studied interfacial properties so far are contact stability and dendrite nucleation and growth.…”
mentioning
confidence: 99%
“…The optimal amount of active material is around 90 %; binder and conductive additives (carbon black) range between 2 and 8 %, depending on the battery type and conditions of use. Besides the established carbon black, perspective conductive additives such as carbon nanotubes, [27] graphene [28] and conductive polymers [29] are studied. Generally, these components allow to increase the weight ratio of the active material, without compromising the conductivity of the composite electrode and thus the rate performance.…”
Section: Electron Transport In Composite Electrodesmentioning
confidence: 99%